(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of modernization and globalization has led to changes in community cultural values, including traditional ceremonies as part of local cultural heritage. This study aims to analyze the concept, functional transformation, and factors influencing the changes in the Kebo-keboan traditional ceremony among the Using community in Alasmalang Village, Singojuruh District, Banyuwangi Regency. The study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings revealed that the Kebo-keboan traditional ceremony was originally conducted as a sacred agrarian ritual intended to seek protection, ward off misfortune, and improve agricultural yields. However, the development of tourism and the influence of modernization have transformed the ceremony into a cultural tourism attraction with economic and entertainment values. Nevertheless, the Using community continues to preserve traditional values and religious elements within the implementation of the Kebo-keboan ceremony as part of Banyuwangi’s local cultural identity.